The VC-1 and H.264 Video Compression Standards for Broadband Video Services - Lee, Jae-Beom; Kalva, Hari (Multimedia Systems and Applications, 2008)
The MPEG committee standardized the MPEG AVC (H.264) video coding standard in May 2003. The standard has since seen strong interest and adoption from the industry. A competing standard developed by Microsoft, referred to as VC-1, was standardized in SMPTE in April 2006. VC-1 is essentially a standardized version of Microsoft's Windows Media Video (WMV-9). Both H.264 and VC-1 are highly efficient compression standards that enable high-quality video services such as IPTV and Blu-ray Disc. H.264 and VC-1 are both mandated for high definition video services on Blu-ray Disc. These two standards are expected to form the basis for a new generation of high-quality broadband video services. The VC-1 and H.264 Video Compression Standards for Broadband Video Services covers these video coding standards, as well as issues in broadband video delivery. No other book about H.264 or VC-1 covers the standards in such detail. This book interprets the complex standards specifications and makes these new technologies accessible. Both authors have more than 12 years experience working on video compression and communications. The VC-1 and H.264 Video Compression Standards for Broadband Video Services is designed for researchers and a professional audience, including video engineers, and practitioners in consumer electronics, telecommunications and media compression industries. This book is also suitable as a secondary text or reference for advanced-level students in computer science and electrical engineering. .